Productivity and production components of safflower genotypes affected by irrigation at phenological stages - Santos, Reginaldo Ferreira; Bassegio, Doglas [UNESP]; de Almeida Silva, Marcelo [UNESP] (Elsevier, 2017)
Drought and the scarce resource of water for irrigation can limit agricultural production under tropical conditions. The objective of this study was to investigate the growth and yield response of safflower genotypes to water deficit in the soil profile during vegetative, flowering and yield formation stages, both in clayey and sandy soils. The experiments were carried out in Engenheiro Coelho, SP, Brazil, in autumn-winter 2014. The experimental design was a randomized block in a factorial arrangement, consisting of the genotypes IMA-2232, IMA-4409, IMA-2109 and IAPAR, and irrigation schemes water deficit (WD), irrigation at the vegetative stage (V), irrigation at the grain formation stage (G), irrigation at the vegetative and flowering (VF) stages, irrigation at the vegetative and grain formation (VG) stages, irrigation at the flowering and grain formation (FG) stages and irrigation at the vegetative, flowering and grain formation (VFG) stages (control). The growth of safflower genotypes, yield components and grain and oil yield were weaken by gradual water restriction at the stages, especially at the vegetative stage in both soils. The water regime with irrigation at the flowering stage and grain formation (FG) only did not reduce the oil content in the genotypes in clayey soil. The IAPAR genotype produced more grains (2.7 Mg ha−1), while the IMA-4409 genotype had higher oil content (42.8%) but they both had similar oil yield (0.75 and 0.79 Mg ha−1, respectively) on the clayey soil with irrigation throughout the cycle (VFG). Oil yield in the sandy soil treatment was similar to that of clayey soil (0.72 Mg ha−1) in VFG, in particular for the IMA-4409 genotype. The IAPAR and IMA-4409 genotypes were generally less sensitive to interruption of water supply at the growth stages. In general, the higher total water storage in soil profile of clayey soil, compared to sandy soil, did not benefit the safflower crop. On an average, irrigation only at vegetative and flowering stage (VG) stages can save 15% of water but with a corresponding 50% reduction in yield, both in clayey soil and sandy soil. The irrigation during the VFG stages might be practiced to attain the highest yield of safflower genotypes.
Keywords: Carthamus tinctorius L.; Oil production; Oilseed; Water shortage; Yield